2020
DOI: 10.3233/jad-200778
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Utility of Actuarial Neuropsychological Criteria Across the Continuum of Normal Aging, Mild Cognitive Impairment, and Dementia

Abstract: Background: Research suggests that actuarial neuropsychological criteria improve the accuracy of mild cognitive impairment (MCI) diagnoses relative to conventional diagnostic methods. Objective: We sought to examine the utility of actuarial criteria relative to consensus diagnostic methods used in the National Alzheimer’s Coordinating Center (NACC) Uniform Data Set (UDS), and more broadly across the continuum of normal aging, MCI, and dementia. Methods: We compared rates of cognitively normal (CN), MCI, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This is especially vital as poor diagnostic stability renders high reversion rates, poor identification of factors associated with reversion and dementia progression. One ultimate goal in MCI research is to achieve precise predictions for progression, in order to enable successful drug interventions [58]. Finally, our results express important aspects of daily social stimulation, the severity of the cognitive impairment, the role of alcohol consumption, BMI, and age on predicting the future path of those diagnosed with MCI.…”
Section: Discussionmentioning
confidence: 76%
“…This is especially vital as poor diagnostic stability renders high reversion rates, poor identification of factors associated with reversion and dementia progression. One ultimate goal in MCI research is to achieve precise predictions for progression, in order to enable successful drug interventions [58]. Finally, our results express important aspects of daily social stimulation, the severity of the cognitive impairment, the role of alcohol consumption, BMI, and age on predicting the future path of those diagnosed with MCI.…”
Section: Discussionmentioning
confidence: 76%
“…These findings are consistent with recent work from our laboratory that compared actuarial vs consensus diagnoses using data from the NACC Uniform Data Set 40 ; we found that approximately one-third of individuals diagnosed as CN by consensus diagnosis met neuropsychological criteria for MCI. 41 Results of the current study have several important clinical and research implications. First, our findings show that the ADRC's method of consensus diagnosis underestimates MCI in its participant sample.…”
Section: Discussionmentioning
confidence: 82%
“…These findings are consistent with recent work from our laboratory that compared actuarial vs consensus diagnoses using data from the NACC Uniform Data Set 40 ; we found that approximately one-third of individuals diagnosed as CN by consensus diagnosis met neuropsychological criteria for MCI. 41…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maltreatment in the context of psychological assessment can take the form of diagnostic accuracy errors that result in overdiagnosis (Graves et al, 2020), particularly for historically minoritized older adults (Devlin et al, 2022). For example, there is a discrepancy between Black older adults compared to older white adults who meet classification for mild cognitive impairment instead of normal cognition when using demographically adjusted z scores (i.e., actuarial criteria) versus consensus criteria that incorporate screening measures, subjective cognitive and functional complaints, and clinician judgment (Graves et al, 2022).…”
Section: Maltreatment By the Medical Fieldmentioning
confidence: 99%